Ample felicitous wave structures for fractional foam drainage equation modeling for fluid-flow mechanism - Yokus, Asif; Durur, Hulya; Duran, Serbay; Islam, Md Tarikul (Springer Heidelberg, 2022)
In this study, traveling wave solutions have been explored with the newly developed improved tanh method and modified (1/G')-expansion method for the Fractional foam drainage equation, which is famous for modeling physical phenomena such as heat conduction and acoustic waves. Abundant solutions are successfully achieved which have not been appeared ever in the literature. The found solutions are represented graphically to bring out the appearances of different types solitons. In addition, three important points are highlighted in the result and discussion section. First, the comparison of the applied methods, second, the association of the obtained solutions with the literature, and finally the effect of the change in the parameters with physical properties on the wave behavior are discussed.
Keywords: Improved tanh method; Modified (1/G ')-expansion method; Fractional foam drainage equation; Exact solutions